Study on Failure Mechanism and Control Technology of Roadway Surrounding Rock under Complex Occurrence Coal Seam - Hai Wu; Jiaren Chen; Xu Gao; Tao Ling; Xuan Zhang; Qian Jia (Geofluids)
Aiming at the characteristics of large deformation and long deformation time under the mining influence of the 2254 east floor roadway surrounding rock, which under the condition of complex coal occurrence in Jiahe Mine. Through the actual measurement, it is found that the mineral composition of the roadway surrounding rock is mainly siderite, and it also contains 9.52% of kaolinite minerals, and the surrounding rock is relatively weak. Through drilling and peeping, it is found that the roadway surrounding rock is mainly thin-layered, and a large number of fissures are developed in the surrounding rock near the surface of the roadway. Through the in situ stress test, it is concluded that the in situ stress field of Jiahe Mine is dominated by horizontal stress, the minimum principal stress is vertical principal stress, and the lateral pressure coefficient exceeds 2, causing serious damage to the two sides of the roadway. Using the gas drainage drilling data of the 2254 east floor roadway and using SketchUp and Rhino software, the complex geological occurrence model of the coal seam above the roadway was constructed, and on this basis, the FLAC3D numerical calculation model was constructed. The analysis results show that the plastic zone of the roadway surrounding rock is large, the bolt anchoring section is within the plastic zone, and the control effect on the deformation of the roadway surrounding rock is poor. Therefore, a comprehensive support method of “reserved deformation, anchor rod, metal mesh, shotcrete, grouting anchor cable, and full-section grouting” is proposed. The monitoring results of the surrounding rock deformation of the roadway 12 months after construction show that the support scheme can effectively control the deformation of the roadway surrounding rock. The research results provide a reference for the stability control of similar roadways.